Association between atherogenic index of plasma with all-cause and cardiovascular mortality in individuals with Cardiovascular-Kidney-Metabolic syndrome - Qianrong Zheng; Zhenyang Cao; Jiayi Teng; Qian Lu; Pan Huang; Jianghua Zhou (Cardiovascular Diabetology)
Abstract Background Cardiovascular-Kidney-Metabolic (CKM) syndrome, as a new clinical concept, emphasizes the multifaceted interaction between metabolic disorders, chronic kidney disease (CKD), and cardiovascular disease (CVD). Some evidence suggests atherogenic index of plasma (AIP) is strongly linked to cardiovascular mortality. However, data on its association with mortality across CKM syndrome remain scarce. Our study aimed to investigate the association between AIP and all-cause and cardiovascular mortality among individuals with CKM syndrome. Methods This study included 15,703 participants with CKM syndrome from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. The AIP index is calculated as log10(triglycerides/high-density lipoprotein cholesterol [TG/HDL-C]). Mortality outcomes were determined by linking NHANES participants with the National Death Index (NDI), with follow-up data available through December 31, 2019. Kaplan–Meier (K–M) survival curves, Cox regression analysis, restricted cubic spline (RCS) and subgroups analysis were used to explore the relationship between AIP levels and mortality in individuals with CKM syndrome. Results Over a median follow-up of 7.67 years, a total of 1570 deaths were documented, including 344 cardiovascular deaths. Kaplan-Meier survival analysis demonstrated that the lowest all-cause and CVD mortality rates were observed in the lowest AIP tertile. Compared with individuals in the lowest AIP tertile, Cox analysis indicated that those in highest tertile were associated with a higher risk of all-cause and CVD mortality (HR = 1.19, 95% CI 1.08–1.31, P < 0.001; HR = 1.38, 95% CI 1.22–1.57, P < 0.001) after adjusting for covariates, respectively. As a continuous variable, AIP levels had an approximate positive linear dose-response relationship with all-cause and CVD mortality. Subgroup analysis revealed no significant interactions with the examined variables, except for gender. Conclusions This study demonstrated that elevated AIP levels in individuals with CKM syndrome are strongly linked to higher mortality risks, notably all-cause mortality in advanced stages and CVD mortality across both non-advanced and advanced stages. These findings further highlight the importance of AIP as a valuable risk biomarker, providing a simple and effective tool for identifying mortality risk in individuals with CKM syndrome. Graphical abstract